Vitamin D3 Suppresses Human Cytomegalovirus-Induced Vascular Endothelial Apoptosis via Rectification of Paradoxical m6A Modification of Mitochondrial Calcium Uniporter mRNA, Which Is Regulated by METTL3 and YTHDF3 - Zhu, Wenbo; Zhang, Hongbo; Wang, Shao (Frontiers in Microbiology, 2022)
HCMV infection can induce apoptosis of vascular endothelial cells, which may be the most important element of development and progression of reported atherosclerosis caused by HCMV. As there are no specific drugs to clear HCMV infection, exploration of relevant drugs and mechanisms that can intervene in HCMV-induced atherosclerosis is urgently needed. The present study confirmed that vitamin D3 protected vascular endothelial cells from HCMV-induced apoptosis by inhibiting endoplasmic reticulum (ER) and mitochondrial apoptosis pathway. Mechanistically, HCMV infection could induce aberrantly elevated m6A modification, especially the increases of methyltransferases-“writers” (METTL3) and m6A binding proteins-“readers” (YTHDF3) . METTL3 methylates MCU, the main contributor to HCMV-induced apoptosis of vascular endothelial cells, at three m6A residues in the 3’-UTR, which promotes the association of the YTHDF3 with methylated MCU mRNA and subsequently increases the translation and expression of MCU. Further analsis show that ALKBH5 is the demethylases-“eraser” of MCU mRNA, which can negatively regulate the m6A modification process of MCU. Conversely, vitamin D downregulated the METTL3 by inhibiting the activation of AMPK, thereby inhibiting the m6A modification of MCU and cell apoptosis. Our findings extend the understanding of m6A driven machinery in virus-induced vascular endothelium damage and highlight the significance of vitamin D in the intervention of HCMV-induced atherosclerosis.